2002
DOI: 10.1099/00207713-52-5-1767
|View full text |Cite
|
Sign up to set email alerts
|

Halomonas halocynthiae sp. nov., isolated from the marine ascidian Halocynthia aurantium.

Abstract: NOTE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Species of the genus Halomonas are metabolically very diverse and can grow between 1% and 26% salt, with optimum growth around 9% salt (Mata et al , 2002; Arahal et al , 2007). They were previously isolated from various saline and hypersaline environments, such as evaporation ponds (Baati et al , 2008), saline wetland (Martínez‐Cánovas et al , 2004), soil (Quillaguaman et al , 2004) and soda lake (Duckworth et al , 2000), but also from Antarctic lakes (Franzmann et al , 1987), paintings (Heyrman et al , 2002), sea ascidians (Romanenko et al , 2002) and a sea anemone (Xiao et al , 2009). Their presence has also been confirmed in association with Artemia from the Great Salt Lake (UT) by clone library analysis, but only in association with adult animals and not with encysted embryos (Riddle et al , 2007, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Species of the genus Halomonas are metabolically very diverse and can grow between 1% and 26% salt, with optimum growth around 9% salt (Mata et al , 2002; Arahal et al , 2007). They were previously isolated from various saline and hypersaline environments, such as evaporation ponds (Baati et al , 2008), saline wetland (Martínez‐Cánovas et al , 2004), soil (Quillaguaman et al , 2004) and soda lake (Duckworth et al , 2000), but also from Antarctic lakes (Franzmann et al , 1987), paintings (Heyrman et al , 2002), sea ascidians (Romanenko et al , 2002) and a sea anemone (Xiao et al , 2009). Their presence has also been confirmed in association with Artemia from the Great Salt Lake (UT) by clone library analysis, but only in association with adult animals and not with encysted embryos (Riddle et al , 2007, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The genus Halomonas is the largest genus in the family Halomonadaceae and was first proposed by Vreeland et al (1980). Species of the genus Halomonas have been isolated from diverse saline environments such as salterns, saline soils, estuarine water, salt lakes, deep sea, seafood and marine invertebrates (Vreeland et al , 1980; Ventosa et al , 1998; Romanenko et al , 2002; Yoon et al , 2002; Kaye et al , 2004; Lim et al , 2004; Arahal & Ventosa, 2006; Arenas et al , 2009; Guan et al , 2010; Guzmán et al , 2010; Kim et al , 2010; Wang et al , 2012; Jeong et al , 2013). At the time of writing, the genus Halomonas comprised 90 recognized species (Parte, 2015).…”
mentioning
confidence: 99%
“…The genus Halomonas belongs to the family Halomonadaceae within the Gammaproteobacteria and at the time of writing comprised 35 species that had been isolated mainly from saline or hypersaline environments (Arahal et al, 2002;Bouchotroch et al, 2001;Dobson & Franzmann, 1996;Garcia et al, 2004;Lee et al, 2005;Lim et al, 2004;Martínez-Cánovas et al, 2004;Martínez-Checa et al, 2005;Mata et al, 2002;Mormile et al, 1999;Quillaguaman et al, 2004;Romanenko et al, 2002;Ventosa et al, 1998;Vreeland et al, 1980;Yoon et al, 2001Yoon et al, , 2002 or from unusual habitats such as dry mural paintings (Heyrman et al, 2002) and deep-sea hydrothermal vents (Kaye et al, 2004). Phylogenetic analysis using the 16S and 23S rRNA gene sequences and phenotypic studies demonstrated that this genus is very heterogeneous (Arahal et al, 2002;Mata et al, 2002).…”
mentioning
confidence: 99%